Click, Ship, Regret: E-Commerce Strategies Behind Compulsive Fashion Buying - Librina Tria Putri; Nofrizal Nofrizal; Rafidianto Wibisono; Afvan Aquino; Aznuriyandi Aznuriyandi; Richa Afriana Munthe (Binus Business Review, 2026)
E-commerce has become a widely used platform around the world to obtain fashion products in an easy and efficient way. However, there is a negative impact on consumer behavior, namely excessive consumption. It can harm the environment and consumers’ mental health if not addressed. The research aimed to examine the roles of free shipping and Cash on Delivery (COD) in Fear of Missing Out (FOMO) and compulsive buying, as well as the mediating role of FOMO on e-commerce sites such as Shopee, Tokopedia, Lazada, and Zalora. A quantitative approach was used, with an online survey via Google Forms distributed via social media such as WhatsApp, Instagram, and Facebook, involving 467 e-commerce customers selected through purposive sampling. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that free shipping does not significantly encourage FOMO or compulsive buying. In contrast, the COD feature has a significant impact on FOMO and compulsive buying. In addition, FOMO positively mediates the relationship between COD and compulsive buying, but not between free shipping and compulsive buying. These findings make important contributions to the theory of FOMO and compulsive buying in e-commerce, to consumer and e-commerce education on digital marketing strategy algorithms, and to the development of environmentally friendly waste management strategies. The research is particularly novel in the context of Indonesian e-commerce, as it simultaneously examines four. Furthermore, FOMO is tested as a mediating variable.